Unveiling the shadows: obstacles, consequences, and challenges of information opacity in healthcare systems - Majid Alizadeh; Nazila Azizi; Samireh Mahdavi; Fouad Baghlani (Philosophy, Ethics, and Humanities in Medicine)
Abstract Introduction Information transparency in healthcare systems is critical for ensuring public trust, enhancing service quality, and reducing costs. However, many countries face significant challenges concerning information opacity, which leads to inequality, discrimination, and increased risks for patients and healthcare providers. This study aims to explore the obstacles, consequences, and challenges of information opacity in healthcare systems, along with proposing solutions for improvement. Method This review synthesized findings from scientific literature, including articles, reports, and governmental sources, to investigate how the lack of information transparency affects healthcare performance and public trust. A comprehensive search was conducted across major databases such as PubMed, Scopus, and Google Scholar, utilizing relevant keywords. Selection criteria focused on the relevance, quality, and timeliness of the sources, leading to a critical analysis of the extracted data through thematic synthesis. Findings The study identifies several key consequences of information opacity, including a decrease in public trust, reduced service quality, increased corruption, and heightened healthcare costs. The findings align with existing literature that highlights the importance of transparency for effective decision-making and accountability in healthcare systems. Furthermore, obstacles to achieving transparency were identified, such as difficulties in accessing necessary information, privacy concerns, commercial interests, and the need for systemic reforms in healthcare financing. Discussion The implications of this study underscore the necessity for clear policies and procedures regarding information dissemination in healthcare. The proposed framework for improving transparency includes establishing robust communication channels, enhancing public access to information, fostering a culture of accountability, and leveraging emerging technologies like blockchain and artificial intelligence. Addressing these challenges is essential for building trust and improving healthcare outcomes. Conclusion Enhancing information transparency within healthcare systems is vital for improving public trust and service quality. This study provides a foundational framework for policymakers to implement necessary changes, promoting a more equitable and efficient healthcare environment. Future research should focus on evaluating the effectiveness of these proposed measures in diverse healthcare contexts, particularly by integrating theoretical frameworks such as stakeholder theory and institutional theory.